2006
DOI: 10.1080/00288330.2006.9517437
|View full text |Cite
|
Sign up to set email alerts
|

A review of rotenone use for the control of non‐indigenous fish in Australian fresh waters, and an attempted eradication of the noxious fish,Phalloceros caudimaculatus

Abstract: Rotenone has been used as a piscicide in Australia for c. 45 years. In freshwater systems this use has focused on the control of non-indigenous fish species. Little of this use has been registered, reported or documented and Australian fisheries researchers and managers are forced to rely on international literature. This paper reviews all available documentation relating to rotenone use in Australia, before discussing some planning and application issues that may be faced by those considering rotenone use. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…The distribution of P. parva in the UK in 2005 ) already meant the chance of achieving their total eradication was difficult, as the complexity and expense of any eradication programme increases as its spatial and temporal extent increases (Genovesi 2005;Rayner and Creese 2006). Thus, the use of a risk-based sustained control programme was more appropriate and enabled resources to be allocated principally to managing those populations in the high-risk, lentic environments.…”
Section: Risk-managed Control Of Pseudorasbora Parva Populations In Tmentioning
confidence: 93%
See 1 more Smart Citation
“…The distribution of P. parva in the UK in 2005 ) already meant the chance of achieving their total eradication was difficult, as the complexity and expense of any eradication programme increases as its spatial and temporal extent increases (Genovesi 2005;Rayner and Creese 2006). Thus, the use of a risk-based sustained control programme was more appropriate and enabled resources to be allocated principally to managing those populations in the high-risk, lentic environments.…”
Section: Risk-managed Control Of Pseudorasbora Parva Populations In Tmentioning
confidence: 93%
“…Rotenone application is, however, non-host specific, so is likely to incur collateral damage in non-target fishes and some invertebrate taxa (Rayner and Creese 2006). This may be problematic, given that the framework considered the presence of conservation-important species that may be adversely affected by rotenone application (Table 1).…”
Section: Risk-managed Control Of Pseudorasbora Parva Populations In Tmentioning
confidence: 98%
“…non-native juveniles), native species reintroduction to the reclaimed habitats followed by habitat restoration activities such as flow restoration, introduction of woody debris or riparian vegetation rehabilitation (Kennard et al, 2005;Rayner, Creese, 2006;Casatti et al, 2009) are all measures that will only be effective if the prevention policies are put into practice.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs naturally in the roots and stems of several plants F. Yang : G. Chen (*) Ministry of Education Key Laboratory of Analysis and Detection for Food Safety, Fujian Provincial Key Laboratory of Analysis and Detection Technology for Food Safety, such as the jicama vine plant. Rotenone is recognized as a useful tool for the sampling and control of fish populations (Rayner and Creese 2006), and it is also widely used as a toxicant to clear aquaculture waters in China. In 2000, it was reported that injecting rotenone into rats might cause the development of symptoms similar to those of Parkinson's disease (Caboni et al 2004), which implies that it is necessary to know the residues of the insecticide can appear.…”
Section: Introductionmentioning
confidence: 99%